Disentangling the NIR/optical emission of the black hole XTE J1650-500 during outburst - Curran, Peter; Chaty, S.; Heras, J. (EDP Sciences, 2012)
Context: While the sources of X-ray and radio emission in the different states of low-mass X-ray binaries are relatively well understood, the origin of the near-infrared (NIR) and optical emission is more often debated. It is likely that the NIR/optical flux originates from an amalgam of different emission regions, because it occurs at the intersecting wavelengths of multiple processes. Aims: We aim to identify the NIR/optical emission region(s) of one such low-mass X-ray binary and black hole candidate, XTE J1650−500, via photometric, timing, and spectral analyses.Methods: We present unique NIR/optical images and spectra, obtained with the ESO-New Technology Telescope, during the peak of the 2001 outburst of XTE J1650−500. Results: The data suggest that the NIR/optical flux is due to a combination of emission mechanisms including a significant contribution from X-ray reprocessing and, at early times in the hard state, a relativistic jet that is NIR/radio dim compared to similar sources. Conclusions: The jet of XTE J1650−500 is relatively weak compared to that of other black hole low-mass X-ray binaries, possibly because we observe as it is being “turned off” or quenched at the state transition. While there are several outliers to the radio-X-ray correlation of the hard state of low-mass X-ray binaries, XTE J1650−500 is the first example of an outlier to the NIR/optical-X-ray correlation.